2011
DOI: 10.1152/physiolgenomics.00138.2010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal genomewide expression profiling of DSS colitis reveals novel inflammatory and angiogenesis genes similar to ulcerative colitis

Abstract: Dextran sodium sulfate (DSS)-induced colitis is widely used to study pathological mechanisms and potential treatments of inflammatory bowel disease. Because temporal changes in genome expression profiles remain unknown in this model, we performed whole genome expression profile analysis during the development of DSS colitis in comparison with ulcerative colitis (UC) specimens to identify novel and common responses during disease. Colon tissue from DSS-treated mice was collected at days 0, 2, 4, and 6. Half of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 46 publications
(47 reference statements)
4
77
0
Order By: Relevance
“…Consistent with a functional regulatory role, genomic regions that exhibit the most dynamic decrease in enhancer chromatin structure were located near genes with reduced transcript levels upon inflammation (20). Conversely, regions that gained enhancer chromatin signal were near genes with increased expression levels upon inflammation (Fig.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Consistent with a functional regulatory role, genomic regions that exhibit the most dynamic decrease in enhancer chromatin structure were located near genes with reduced transcript levels upon inflammation (20). Conversely, regions that gained enhancer chromatin signal were near genes with increased expression levels upon inflammation (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Gene set enrichment analysis (GSEA) (19) was performed using public gene expression data from DSS-treated mice (GEO series GSE22307; expression data reported for C57BL/6J male mice, 12 to 14 weeks old, treated with 3% DSS for 6 days, and controls, with whole-colon tissue RNA measured using Affymetrix 430_2.0 arrays [20]). These GSE22307 expression data were compared to genes within 10 kb of the 1,000 most positive or 1,000 most negative NSD-scoring chromatin regions.…”
mentioning
confidence: 99%
“…Briefly, the experimental fish were fed twice daily with radiation-sterilized frozen red worms at ∼3% of their body weight. Then, they were administered with 500 ml 5% DSS (molecular mass of [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] kDa; MP Biomedicals) via oral perfusion once a day just before the second feeding time to ensure that the intestines of the fish were empty when they received the drug. The DSS administration was performed for 7 consecutive days to induce colitis.…”
Section: Dss-induced Tetraodon Colitis Modelmentioning
confidence: 99%
“…It has been reported that DSS treatment leads to superficial inflammatory changes in the mucosa and submucosa of colon tissues in mouse models with various histopathological features similar to that seen in human UC (36,(41)(42)(43)(44)(45). Therefore, the DSS-induced colitis model has become one of the most widely used experimental models for human UC research (42).…”
Section: Dss-induced Tetraodon Colitis Modelmentioning
confidence: 99%
“…RNA isolation and quantitative RT-PCR Quantitative RT-PCR analysis was performed as previously reported by our laboratory [20]. Total RNA was isolated using a kit (RNeasy Isolation Kit; Qiagen, Hilden, Germany).…”
Section: Animalsmentioning
confidence: 99%